FEATURES OF IMPLEMENTATION AND ENVIRONMENTAL POLICY RISKS - Yefimov , Y. (Theory and Practice of Public Administration, 2020)
Government policy affects the development and use of economic incentives, changes in the environmental values of society, as well as the usage of energy and resources by government agencies. The implementation of such policy is extremely relevant, since environmental threats pose problems for public or collective benefits that cannot be solved by private actions alone. Topical issues that require improved approaches to identifying the features of ensuring sustainable development of countries by means of environmental policy are highlighted. The issue of trade-off between economic development and environmental security is considered. Areas, distortions or shortcomings in which environmental problems are theoretically substantiated. These include: 1) scientific knowledge and its usage; 2) the economy and the incentives used in economic policy; 3) environmental values and ethics. In order to determine the directions of formation and implementation of public environmental policy in the context of the current global environmental challenges, the specific nature of measures to address environmental problems at the national level is analyzed. The substantive characteristics of different types of public environmental policy are determined. Attention is drawn to the need for a comprehensive analysis of social, economic and environmental risks in environmental policy-making. Improving societal responses to environmental problems and policies to address them requires careful evaluation and serious efforts to determine which types of solutions are most promising and have an acceptable level of risk.